Living on the edge: transfer and traffic of E. coli in a confined flow. Issue 31 (21st August 2015) - Figueroa-Morales, Nuris; Leonardo Miño, Gastón; Rivera, Aramis; Caballero, Rogelio; Clément, Eric; Altshuler, Ernesto; Lindner, Anke
<x xml:space="preserve">Abstract</x> Systematic experiments quantify the robust upstream motion of E. coli bacteria at the edges of microfluidic channels.